Optimal Location of Voltage Regulation and Reagent Compensation Equipment for Medium Voltage Feeders, Using Evolutionary Algorithms - Carreno Muñoz, Carlos (2022)
Currently, voltage regulation in distribution networks plays an important role in the economic growth of a country and human progress, given that a good quality of electrical service delivered to end users has a direct effect on the productivity of the industries, education, health, communication services and drinking water supply. This article proposes a short-term solution to the problem of low voltage in medium voltage networks, with the optimal input of voltage regulation equipment through a genetic algorithm in Matlab that will evaluate the electrical parameters of the network before and after to install the compensation equipment, complying with the current regulation Arconel 005/18 in the Ecuadorian electricity sector